Nurse-Led Telephone Follow-up. Issue 3 (May 2015) - Smits, Anke; Lopes, Alberto; Das, Nagindra; Bekkers, Ruud; Kent, Emma; McCullough, Zoe; Galaal, Khadra
<x xml:space="preserve">Abstract</x> Background: Nurse-led follow-up (NLFU) has been identified as a suitable means of follow-up care in cancer patients, and its acceptability has already been demonstrated in other areas of cancer care. Objectives: The objectives of this study were to evaluate the effect of NLFU on quality of life and patient satisfaction compared with conventional follow-up (CFU) in women treated for endometrial cancer and to evaluate the feasibility of NLFU, in terms of patient acceptance and referral to consultant clinic. Methods: Participants included women diagnosed with endometrial cancer between 2008 and 2013. At time of study, 118 women were receiving NLFU, and 178 women were receiving CFU. Quality of life and patient satisfaction were evaluated through the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire and the In-patient Satisfaction With Care Measure questionnaires. Feasibility of NLFU was retrospectively assessed through patient's records. Results: Seventy-eight women in NLFU and 112 women in CFU completed the questionnaires. Quality-of-life outcomes and satisfaction levels did not differ between both forms of follow-up. Almost all women in NLFU (98%) found NLFU an acceptable alternative to CFU. Conclusion: Women receiving NLFU reported similar quality of life and satisfaction with care as did women in CFU, making it a promising alternative for follow-up care of women with endometrial cancer. Implications for Practice: Options are improved for women with endometrial cancer by offering alternative follow-up strategies within the national healthcare.